Impact of Economic Growth and FDI on Indonesia Environmental Degradation: EKC and Pollution Hypothesis Testing - Dominikus Leonardo; Muhammad Maulana; Justin Hartanto (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2023)
This study examines the impact of economic growth and FDI on environmental degradation in Indonesia through a two-hypotheses model. Environmental degradation is a crucial matter that needs attention and is often associated with economic growth and the FDI required by developing countries. Based on the externality theory, this study uses the EKC hypothesis, followed by pollution haven vs. pollution halo. With time series data from 1980–2021, two hypothesis models were estimated using the error correction method. This study's results support the EKC and pollution haven hypotheses. First, for the EKC hypothesis model, this study found that economic growth at an early stage increases environmental degradation, but economic growth beyond the turning point would reduce ecological degradation. Besides testing the EKC hypothesis, renewable energy consumption can reduce environmental degradation caused by carbon emissions. Second, for the pollution hypothesis model, it's been found that increased FDI can increase ecological degradation, thereby supporting a pollution haven. This research suggests that policymakers should require foreign investors to apply the green economy concept supported by a green taxonomy and then provide fiscal incentives to those who do so.